Asthma in children and adolescents in Brazil: contribution of the International Study of Asthma and Allergies in Childhood (ISAAC) - Solé,Dirceu (2014)
Objective: To assess asthma among Brazilian pediatric population applying the International Study of Asthma and Allergies in Childhood (ISAAC), an internationally standardized and validated protocol.Data sources: ISAAC was conceived to maximize the value of epidemiologic studies on asthma and allergic diseases, establishing a standardized method (self-applicable written questionnaire and/or video questionnaire) capable to facilitate the international collaboration. Designed to be carried out in three successive and dependent phases, the ISAAC gathered a casuistic hitherto unimaginable in the world and in Brazil. This review included data gathered from ISAAC official Brazilian centers and others who used this method.Data synthesis: At the end of the first phase, it has been documented that the prevalence of asthma among Brazilian schoolchildren was the eighth among all centers participating all over the world. Few centers participated in the second phase and investigated possible etiological factors, especially those suggested by the first phase, and brought forth many conjectures. The third phase, repeated seven years later, assessed the evolutionary trend of asthma and allergic diseases prevalence in centers that participated simultaneously in phases I and III and in other centers not involved in phase I.Conclusions:In Brazil, the ISAAC study showed that asthma is a disease of high prevalence and impact in children and adolescents and should be seen as a Public Health problem. Important regional variations, not well understood yet, and several risk factors were found, which makes us wonder: is there only one or many asthmas in Brazil?